(untitled) (Foro de Educacion, 2022)
This research proposes an approach to the meaning of digital competences indicated by UNESCO (2008) according to the educational culture proposed by the Sumak Kawsay to which Ecuador aspires as a society since 2008. If the concept of digital competences is difficult by itself, the contextualization required by the political and educational culture of this Latin-American country, demands a reflection on the cultural meaning that it should be pursued in an educational legislation that proposes a modern discourse that defends, among other essential principles, the ecological one. Through normative hermeneutics, current issues in its development are discussed, and essential keys for its conceptualization are proposed through the analysis offered by the technological domestication and radical or inclusive training approaches .The consequences of an instrumentalized technological policy, incoherent with the constitutional norm itself and with the cultural context, are discussed. If the stage of technological appropriation is still a challenge in the face of the serious digital divide, the conversion process requires a technological dialectic that starts from a process of ecological conscience that is legally required, and in which cultural and social meanings may necessarily be included beyond the ones based on western contexts. Thus, the need to incorporate keys for a pedagogy that discusses the role of radical themes in Ecuadorian education such as egocentrism, or the definition of person as a member of nature among others, is made visible from the Ecuadorian educational standards themselves.